#WomenTechLit - Mencía, María (Computing literature, 2017)
This book of electronic literature (e-lit) brings together pioneering and emerging women whose work has earned international impact and scholarly recognition. It extends a historical critical overview of the state of the field from the diverse perspectives of twenty-eight worldwide contributors. It illustrates the authors' scholarly interests through discussion of creative practice as research, historical accounts documenting collections of women's new media art and literary works, and art collectives. It also covers theoretical approaches and critical overviews, from feminist discourses to close readings and "close-distant-located readings" of pertinent works in the field. #WomenTechLit includes authors from Latin America, Russia, Austria, Ireland, Spain, France, Italy, Portugal, Slovakia, Czech Republic, Poland, United Kingdom, Australia, Canada, and the US. This volume will be a useful reference for educators, practice-based researchers, and scholars, not only of electronic literature but also in the adjacent areas of language art, new media art practices, digital humanities, and feminist studies.